2009
DOI: 10.1093/jb/mvp096
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin B Identified as an Inhibitor of Alternative NADH Dehydrogenase and Malate: Quinone Oxidoreductase from the Gram-positive Bacterium Mycobacterium smegmatis

Abstract: Tuberculosis is the leading cause of death due to a single infectious agent in the world and the emergence of multidrug-resistant strains prompted us to develop new drugs with novel targets and mechanism. Here, we screened a natural antibiotics library with Mycobacterium smegmatis membrane-bound dehydrogenases and identified polymyxin B (cationic decapeptide) and nanaomycin A (naphtoquinone derivative) as inhibitors of alternative NADH dehydrogenase [50% inhibitory concentration (IC(50)) values of 1.6 and 31 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 44 publications
1
47
0
Order By: Relevance
“…In fact, Vibrio cholerae treated with polymyxin B exhibits an increase in the transcriptional levels of rpoE, the sigma factor involved in envelope and oxidative stress responses (37). Interestingly, previous studies have indicated that polymyxin B treatment can induce aberrant oxidative respiration (31,40,42). In organisms with no experimentally identified CpxAR envelope stress-sensing two-component system, such as A. baumannii and F. novicida, this envelope stress response may be triggered by other, as-yet-unidentified, sensory systems.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Vibrio cholerae treated with polymyxin B exhibits an increase in the transcriptional levels of rpoE, the sigma factor involved in envelope and oxidative stress responses (37). Interestingly, previous studies have indicated that polymyxin B treatment can induce aberrant oxidative respiration (31,40,42). In organisms with no experimentally identified CpxAR envelope stress-sensing two-component system, such as A. baumannii and F. novicida, this envelope stress response may be triggered by other, as-yet-unidentified, sensory systems.…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify new inhibitors for alternative respiratory enzymes (i.e., enzymes that are not present in human mitochondria), we screened the Kitasato Institute for Life Sciences Chemical Library [30] with the following enzymes: cytochrome bd quinol oxidase from Escherichia coli [31, 32], bacterial cyanide-insensitive oxidase (CIO, a variant of cytochrome bd) and a single-subunit NADH dehydrogenase (NDH-2) from the acetic acid bacterium Gluconobacter oxydans [33,34], and NDH-2 and malate: quinone oxidoreductase (MQO) from Mycobacterium smegmatis [35] and Pseudomonas aeruginosa [36]. Cytochrome bd and CIO are widely distributed among bacteria and play an important role in microaerophilic respiration and protection against oxygen stress and in the survival and adaptation of pathogenic bacteria [37][38][39].…”
Section: Screening Of a Natural Antibiotics Librarymentioning
confidence: 99%
“…Plasmodium species possesses a group 2 MQO, in contrast to bacterial group 1 MQO [127]. P. falciparum MQO (PfMQO) is part of both mitochondrial ETC and TCA cycle, substituting other mitochondrial malate dehydrogenases (MDH) [111,112,128].…”
Section: Malate-quinone Oxyreductase (Mqo)mentioning
confidence: 99%